Retrospective study on bovine clinical mastitis and associated milk loss during the month of its peak occurrence at the National Dairy Farm in the Emirate of Abu Dhabi, United Arab Emirates - Ameni, Gobena; Bayissa, Berecha; Zewude, Aboma; Degefa, Berhanu Adenew; Mohteshamuddin, Khaja; Kalaiah, Gopala; Alkalbani, Meera Saeed; Eltahir, Yassir Mohammed; Elfatih Hamad, Mohamed; Tibbo, Markos (Frontiers in Veterinary Science, 2022)
Commercial dairy establishments are relatively young in the United Arab Emirates (UAE), and as a result, there is lack of epidemiological data on mastitis in dairy farms. A retrospective data of seven years (2015-2021) were used to estimate the cumulative average monthly incidence rate of bovine clinical mastitis and evaluate associated milk loss at the National Dairy Farm. Data were extracted from the records of lactating dairy cows (n = 1300 to 1450) and analyzed using repeated measure and one-way ANOVA, nonparametric Spearman correlation, paired and unpaired t tests. The highest average cumulative monthly incidence rate was 49 cases per 1000 cows-year that was recorded in 2019 while the lowest was 19 cases per 1000 cows-year in 2021. The cumulative average monthly incidence rate of clinical mastitis significantly (p < 0.001) varied among the seven years. The cumulative average monthly incidence rate was associated with average monthly humidity (p<0.01) and average monthly rainfall (p <0.05); however, it was not associated with the average monthly temperature (p>0.05). The average daily milk yield of cows with clinical mastitis (Mean±SEM; 18.6±0.54 kg) was significantly (p < 0.001) lower than the average daily milk yield of clinical mastitis free cows (40.5±0.29 kg). The largest average monthly milk loss due to clinical mastitis was 5% of the average total monthly milk production in 2019 while the lowest was 2% of the average total monthly milk production in 2021. The result of the study indicated the direct influence of weather conditions such as increased rainfall and humidity, which caused an upsurge in the incidence rate of clinical mastitis, leading to an increased loss in milk and hence the economy of the dairy farm. Proactive preventive measures along with good dairy farm practices that help mitigate the impacts of harsh weather conditions are recommended.